The problem of political socialization in ethnic groups - G. G. Khachatryan (Контуры глобальных трансформаций: политика, экономика, право, 2018)
Article deals with the problem of political socialization in ethnic groups. The questions of the formation of political views within the family, schools with ethno-cultural component, cultural centers are treated. The issue of fragmentation of ethnic communities and the existence of mechanisms that target disintegration is addressed.